El aprendizaje moral de los individuos y de las corporaciones: Las etapas de Kohlberg, la cultura organizacional y los codigos de etica - Luisa Montuschi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2006)
– Can ethics be taught? This is an old issue and many people doubt if business ethics courses are of any value. After all the ability to deal with moral issues is developed at very early ages. This is so according to the research carried on by Harvard psychologist Lawrence Kohlberg who identifies different stages of moral development from childhood years. Anyway there is evidence that ethics can be learned in adult age. This means that individuals can become more aware about the ethical aspects of many situations that arise in corporate life. Which doesn't necessarily mean that individuals or corporations are more ethically concerned as a consequence of business ethics courses. But in any case it seems that those courses have had a discernible effect on the organizational culture and on the ethical codes of corporations. Which it is not to say that their ethical behavior has dramatically improved.
Keywords: 330